Denial, Trivialization and Relegation of Pluralism: The Challenges of Managing Diversity in Multi–religious Malaysia and Indonesia - Ibrahim, Azhar (Studia Islamika, 2012)
This article attempts to discuss the various societal responses to religious diversity and pluralism in Malaysia and Indonesia. Its focus is on the Muslim–majority nations of Indonesia and Malaysia, where the idea of religious pluralism among Muslims has taken various shapes. While the state’s management of pluralism is so far characterized by politics of expediency and accommodation to ensure stability, law and order, and harmony, it is the societal or community responses that matter most. Advancing and nurturing the ideas of religious pluralism in social and religious discourse requires commitment in persistency and planning. This, in turn, calls for the need to know how the ideas of pluralism and religious diversity have been understood in society. The challenge of nurturing a substantive pluralism in society warrants recognition and support. This can be made in the realms of theological discourse, political will, educative approach, as well as institutional supportDOI: 10.15408/sdi.v19i3.355